Guidelines for the use of copper alloys in seawater - Tuthill, Arthur H. (Nickel Development Institute ; Copper Development Association, 1987)
This reference is helpful in selecting materials for marine service. This review updates and extends those summaries for copper-base alloys, many of which were not included in the earlier work.